A multidimensional view of racial differences in access to prostate cancer care. Issue 22 (20th July 2017) - Pollack, Craig Evan; Armstrong, Katrina A.; Mitra, Nandita; Chen, Xinwei; Ward, Katelyn R.; Radhakrishnan, Archana; Wong, Michelle S.; Bekelman, Justin E.; Branas, Charles C.; Rhodes, Karin V.; Grande, David T.
Abstract : BACKGROUND: Racial disparities in prostate cancer treatment and outcomes are widespread and poorly understood. In the current study, the authors sought to determine whether access to care, measured across multiple dimensions, contributed to racial differences in prostate cancer. METHODS: The Philadelphia Area Prostate Cancer Access Study (P 2 Access) included 2374 men diagnosed with localized prostate cancer between 2012 and 2014. Men were surveyed to assess their experiences accessing care (response rate of 51.1%). The authors determined appointment availability at 151 urology practices using simulated patient telephone calls and calculated travel distances using geospatial techniques. Multivariable logistic regression models were used to determine the association between 5 different domains of access (availability, accessibility, accommodation, affordability, and acceptability) and receipt of treatment, perceived quality of care, and physician‐patient communication. RESULTS: There were 1907 non‐Hispanic white and 394 black men in the study cohort. Overall, approximately 85% of the men received definitive treatment with no differences noted by race. Black men were less likely to report a high quality of care (69% vs 81%; P <.001) and good physician‐patient communication (60% vs 71%; P <.001) compared with white men. In adjusted models, none of the 5 domains of access were found to be associated with definitive treatment overall or with radical prostatectomy. All access domains were associated with perceived quality of care and communication, although these domains did not mediate racial disparities. CONCLUSIONS: To the authors' knowledge, the current study presents the first comprehensive assessment of prostate cancer care access, treatment, and patient experience, demonstrating that although access was related to overall perceived quality of care and better physician‐patient communication, it did not appear to explain observed racial differences. Cancer 2017;123:4449‐57 . © 2017 American Cancer Society . Abstract : The current study presents what to the authors' knowledge is the first comprehensive assessment of access to prostate cancer care. The authors report that although access appears to be positively correlated with a higher overall perceived quality of care and better physician‐patient communication, it does not appear to explain observed racial differences.